Crystal structure of a dithiocarbazate diester: E-bis(3-methylbenzyl)-1- (6-methylpyridin-2-yl)ethylidene-carbohydrazonodithioate, C25H27N3S2 - Tayamon, Shahedeh; Tiekink, Edward R. T.; Omar, Siti Aminah; Ravoof, Thahira Begum S. A.; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne (Walter de Gruyter GmbH, 2014)
C25H27N3S2, monoclinic, P21/n (no. 14), a = 8.2943(4) Å, b = 8.5039(4) Å, c = 33.587(2) Å, β = 95.921(4)°, V = 2356.4 Å3, Z = 4, Rgt(F) = 0.0451, wRref(F2) = 0.1340, T = 150 K.